Isolations andAntibacterial Tests of Aloe Vera Endophytic Bacteria (Aloe barbadensis miller) towards Staphylococcus aureus and Eschericia coli - Hildegardis Missa; Olegario De Fatima Lelo Carion; Yolenta Sisilia Enggong; Aloysius Djalo; Sardina Ndukang (Agro Bali : Agricultural Journal, 2023)
Research in the field of microbiology regarding the identification of endophytic bacteria in aloe vera is still rarely carried out while many people in East Nusa Tenggara often use aloe vera to cure diseases. The purpose of this study was to identify the endophytic bacteria Aloe barbadensis miller and to determine its antibacterial ability against the growth of Staphylococcus aureus and Escsherichia coli bacteria.  The research procedures included taking samples using purposive sampling method, isolating endophytic bacteria using streak plate method, testing the antibacterial potential against Staphylococcus aureus and Eschericia coli using the paper disc diffusion method. The results showed that endophytic bacteria found on aloe vera leaves were marked by the growth of several bacterial colonies on Murashige-Skoog media with different shapes and colors, then the colonies were separated and 8 isolates were obtained with isolate codes C1B, C2B, C3B, C4B, C5B, C6B, C7B and C8B. The results of the antibacterial potency test showed that isolates C1B, C3B, C5B and C8B had the potential to inhibit the growth of Staphylococcus aureus characterized by the presence of a clear zone on the surface of the media with the largest size being 20 mm in isolate C1B and the smallest clear zone being 7 mm in isolate C8B, while isolate C1B, C3B, C5B and C8B have the potential to inhibit the growth of Eschericia coli bacteria characterized by the presence of a clear zone on the surface of the media with the largest size of 10 mm in isolate C1B and the smallest clear zone of 7 mm in isolate C8B. The conclusion of this study is that endophytic bacteria have been identified in aloe vera and some of these bacteria have antibacterial abilities against the growth of Staphylococcus aureus and Escherichia coli bacteria.